2014
DOI: 10.1155/2014/542395
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic as an Important Tool for Diagnosis and Prognosis for Patients with Hypocellular Primary Myelodysplastic Syndrome

Abstract: We analyzed cytogenetically 105 patients with hypocellular primary MDS and their clinical implications. The main chromosomal abnormalities found were del(5q)/−5, del(6q)/+6, del(7q)/−7, del(11q), and del(17p). Pediatric patients had a higher frequency of abnormal karyotypes compared with adult patients (P < 0,05). From our patients, 18% showed evolution of the disease. The chromosomal abnormalities presented in the diagnosis of patients who evolved to AML included numerical (−7, +8) and structural del(6q), del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Corrêa de Souza et al . recently published a study on cytogenetic changes in a mixed cohort of both pediatric and adult patients with primary hypocellular MDS but did not find specific chromosomal changes associated to hypocellular MDS.…”
Section: Discussionmentioning
confidence: 99%
“…Corrêa de Souza et al . recently published a study on cytogenetic changes in a mixed cohort of both pediatric and adult patients with primary hypocellular MDS but did not find specific chromosomal changes associated to hypocellular MDS.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of hypoplastic MDS documented in literature is 8–20%. 22 , 23 In a recent study of 100 hypoplastic MDS patients, it was observed that these patients have statistically significant lower peripheral blood counts, bone marrow blast percentages and a lower incidence of poor-risk cytogenetic abnormalities, as compared to the non hypoplastic groups. 24 On the contrary, in our cohort of 9.3% (14/150) patients with hypoplastic MDS, the median blast count was 5% and 78% (7/9) of these patients were found to harbor abnormal karyotype ( Supplementary table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Karyotypic abnormalities are seen in approximately 30–50% of patients with MDS and correlated with prognosis [ 5 , 6 , 7 ]. On the other hand, mutations are detectable by next generation sequencing (NGS) in more than 80% of patients with MDS with distinct mutation profiles observed in different MDS subtypes [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Molecular Pathogenesis Of Mdsmentioning
confidence: 99%